The relationship between state Religion and politics - Ardiansyah, Muhammad Rifan (Maliki Interdisciplinary Journal, 2024)
This article discusses how religion, politics, and the state are understood; religion becomes a political identity; the relationship between religion and the state; and the relationship between religion, politics, and the state. The relationship between religion, politics and the state is very close, which are interconnected and have a role in shaping society. Religion has a role in shaping morals and ethics as well as helping a person in facing life's challenges. Religion can become a political identity and can influence one's politics. Religion can provide a consistent worldview and moral values that guide one's behavior in everyday life.